PIM1 and CD79B Mutation Status Impacts the Outcome of Primary Diffuse Large B-Cell Lymphoma of the CNS - Zhou, Jihao; Zuo, Min; Li, Lifeng; Li, Fang; Ke, Peng; Zhou, Yangying; Xu, Yaping; Gao, Xuan; Guan, Yanfang; Xia, Xuefeng; Yi, Xin; Zhang, Xinyou; et al. (Frontiers in Oncology, 2022)
Primary diffuse large B cell lymphoma of the central nervous system (CNS DLBCL) is a rare malignancy with a distinct genetic profile. The clinicopathological significance of the mutation patterns remains unknown. Forty cases of primary CNS DLBCL were subjected to targeted exome sequencing covering 413 genes, including MYD88, CD79B and PIM1. Mutational analysis recognized two groups. The CDP (including CD79B and/or PIM1mutations) group was identified in 27 cases (67.5%), and the non-CDP (without CD79B and PIM1 mutations) group was identified in 13 cases 32.5%). The CDP group tended to occur in older patients (median age 57.0 vs. 48.4 years, p=0.015). Patients in the CDP group had a significantly longer 2-year overall survival (OS) (76% and 40%, p=0.0372) than those in the non-CDP group. Multivariate analysis revealed that age less than 60 years, no MYC and BCL2 double expression, and CDP group were three independent risk factors indicating favorable OS. PyClone analysis revealed the subcloning heterogeneity between the groups. In addition, transcriptional sequencing was successfully performed in 8 cases. A total of 131 genes were significantly differentially expressed between these two groups. The major categories of biological processes that were significantly altered between these two groups related to intracellular metabolism mechanisms. We developed a new molecular classification to divide CNS DLBCL into CDP and non-CDP groups based on CD79B and PIM1 mutational status. Patients with PIM1 and/or CD79B mutations had favorable long-term survival after high-dose methotrexate-based polychemotherapy.